1836 Tenn. Comp. Stat. 673, Shooting, 1821-Chapter 68, § 1 - (:unkn) unknown (My University, 1821)
[A]ny person or persons who shall after the first of January next, shoot at a mark within the bounds of any town, or within two hundred yards of any public road of the first or second class within the state, such person or persons so offending shall be subject to a fine of ten dollars each[.]
Keywords: DISCHARGE